Genome-wide miRNA screening reveals miR-310 family members negatively regulate the immune response in Drosophila melanogaster via co-targeting Drosomycin. - Li, Y.; Li, S.; Li, R.; Xu, J.; Jin, P.; Chen, L.; Ma, F. (Developmental and Comparative Immunology, 2017)
Although innate immunity mediated by Toll signaling has been extensively studied in Drosophila melanogaster, the role of miRNAs in regulating the Toll-mediated immune response remains largely unknown. In this study, following Gram-positive bacterial challenge, we identified 93 differentially expressed miRNAs via genome-wide miRNA screening. These miRNAs were regarded as immune response related (IRR). Eight miRNAs were confirmed to be involved in the Toll-mediated immune response upon Gram-positive bacterial infection through genetic screening of 41 UAS-miRNA lines covering 60 miRNAs of the 93 IRR miRNAs. Interestingly, four out of these eight miRNAs, miR-310, miR-311, miR-312 and miR-313, are clustered miRNAs and belong to the miR-310 family. These miR-310 family members were shown to target and regulate the expression of Drosomycin, an antimicrobial peptide produced by Toll signaling. Taken together, our study implies important regulatory roles of miRNAs in the Toll-mediated innate immune response of Drosophila upon Gram-positive bacterial infection.